(untitled) (Journal of Asian Development Studies, 2019)
Growth is said to be inclusive if it is accessed and shared equitably by all segments of society and a wide-ranging concept in addressing with poverty, inequality and growth of a country. This paper attempts to explain the impact of human capital on inclusive growth of Pakistan with a special focus on CPEC. Investment in human capital and labor force are used as indicators of human capital. Human capital, trade, investment and infrastructure are used as determinants of inclusive growth. Main reason to use these variables as determinant is CPEC. CPEC will particularly affect all these measures in Pakistan. Growth adjusted for inequality is used as a measure of inclusive growth; Data is used for 1987-2015. ARDL approach to cointegration is applied to test long run relation between the variables and error correction mechanism is used to check the correction in short run. The long run relation is negative and significant for investment in human capital, Government investment in education and health appear as cost of Government in developing countries which does not add to economic growth. Positive and significant long run association prevails for trade labor force and FDI with inclusive growth. Infrastructure did not show any significant impact. The short run relation extracted is found mean reverting.